LIFESTYLE RELATIONSHIP AND CONFORMITY WITH CONSUMPTIVE BEHAVIOR IN ADOLESCENTS IN BANYUWANGI CITY PROVINCE OF EAST JAVA - Adinata Topan Priananda; Noviandari Harwanti (SOSIOEDUKASI, 2020)
Research was conducted to determine the relationship between lifestyle and conformity with consumptive behavior in adolescents in Banyuwangi. Consumptive behavior is behavior that is no longer based on rational considerations, but because there is a desire that has reached a level that is no longer rational. Lifestyle is the way a person lives his life which includes activities, interests, and opinions. Conformity is the change in attitudes and behavior of individuals in accordance with the rules formed by the group so that individuals can be accepted and maintained in the group. This type of research is quantitative research. Subjects in the study were 198 teenagers. Data collection methods use three scales, namely consumer behavior, lifestyle and conformity. Analysis of the data used is regression analysis. The results showed that there was a relationship between lifestyle and conformity with consumptive behavior in adolescents in the city of Banyuwangi with r = 0.898 and p = 0.000. Then from the results of the stepwise regression analysis the results show that there is a relationship between lifestyle and consumptive behavior with beta = 0.058, t = 2.268, and p = 0.028. Then in conformity with consumptive behavior there is a relationship with beta = 0.967, t = 35.456, and p = 0.000.